Capturing behavioral indicators of persecutory ideation using mobile technology. (September 2019) - Buck, Benjamin; Hallgren, Kevin A.; Scherer, Emily; Brian, Rachel; Wang, Rui; Wang, Weichen; Campbell, Andrew; Choudhury, Tanzeem; Hauser, Marta; Kane, John M.; Ben-Zeev, Dror
Abstract: Most existing measures of persecutory ideation (PI) rely on infrequent in-person visits, and this limits their ability to assess rapid changes or real-world functioning. Mobile health (mHealth) technology may address these limitations. Little is known about passively sensed behavioral indicators associated with PI. In the current study, sixty-two participants with schizophrenia spectrum disorders completed momentary assessments of PI on a smartphone that also passively collected behavioral data for one year. Results suggested that PI was prevalent (n = 50, 82% of sample) but had infrequent incidence (25.2% of EMA responses). PI was also associated with changes in several passively sensed variables, including decreases in distance traveled (Mkilometers = −1.20, SD = 18.88), time spent in a vehicle (Mminutes = −4.15, SD = 49.59), length of outgoing phone calls (Mminutes = −0.79, SD = 13.13), time spent proximal to human speech (Mminutes = −6.26, SD = 153.03), and an increase in time sitting still (Mminutes = 4.04, SD = 94.69). The present study suggests changes associated with PI may be detectable by passive sensors, including reductions in moving or traveling, and time spent around others or in self-initiated phone conversations. These constructs might constitute risk for PI.